Determinantes y pronóstico de la actividad bursátil del mercado accionario colombiano - Agudelo, David (2018)
Purpose – To study the determinants and evolution of the trading activity in the Colombian Stock Market from 2007 to 2016. Design/methodology/approach – ARMA time series models were used, including several explanatory variables recommended by previous literature. Findings – We find that stock market activity can be predicted to a large extent by its lags, and that positive returns in the last three months, emissions and the VIX index are also explicative variables, as suggested by empirical studies in other countries and theoretical models of market microstructure. These results are robust by using alternative measures of trading activity, total number of trades and turnover. Originality/value – The main contribution of this study is the analysis of the trading activity of the Colombian Stock Market, a critical variable for monitoring the development of any financial market.